Early intervention for very young children with or at high likelihood for autism spectrum disorder: An overview of reviews. (18th May 2022) - Franz, Lauren; Goodwin, Cara D.; Rieder, Amber; Matheis, Maya; Damiano, Diane L.
Abstract : Aim: To identify which interventions are supported by evidence and the quality of that evidence in very young children with or at high likelihood for autism spectrum disorder (ASD) to improve child outcomes. Method: We conducted an overview of reviews to synthesize early intervention literature for very young children with or at high likelihood for ASD. Cochrane guidance on how to perform overviews of reviews was followed. Comprehensive searches of databases were conducted for systematic reviews and meta‐analyses between January 2009 and December 2020. Review data were extracted and summarized and methodological quality was assessed. Primary randomized controlled trial evidence was summarized and risk of bias assessed. This overview of reviews was not registered. Results: From 762 records, 78 full texts were reviewed and seven systematic reviews and meta‐analyses with 63 unique studies were identified. Several interventional approaches (naturalistic developmental behavioral intervention, and developmental and behavioral interventions) improved child developmental outcomes. Heterogeneity in design, intervention and control group, dose, delivery agent, and measurement approach was noted. Inconsistent methodological quality and potential biases were identified. Interpretation: While many early interventional approaches have an impact on child outcomes, study heterogeneity and quality had an impact on our ability to draw firm conclusions regarding which treatments are most effective. Advances in trial methodology and design, and increasing attention to mitigating measurement bias, will advance the quality of the ASD early intervention evidence base. What this paper adds: Naturalistic developmental behavioral interventions, as well as developmental and behavioral interventions, improve child outcomes in autism spectrum disorder (ASD). If only randomized controlled trials are considered, guidelines for early intensive behavioral intervention in younger children should be revisited. The greatest intervention impacts were on proximal, intervention‐specific outcomes. Inadequacies in the quality of the early ASD intervention evidence base were observed. What this paper adds: Naturalistic developmental behavioral interventions, as well as developmental and behavioral interventions, improve child outcomes in autism spectrum disorder (ASD). If only randomized controlled trials are considered, guidelines for early intensive behavioral intervention in younger children should be revisited. The greatest intervention impacts were on proximal, intervention‐specific outcomes. Inadequacies in the quality of the early ASD intervention evidence base were observed. Video Podcast: https://youtu.be/YDqCW‐2XgnU This systematic review is commented on by Abubakar and Kipkemoi on pages 1051–1052 of this issue.